Pengaruh Pelatihan terhadap Kinerja Karyawan PT Tempo Tbk Palembang - Lukman, Muhammad Aditya; Andriana, Isni; Farla, Wita (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
Training is an activity to improve and develop attitudes, behavior, skills and knowledge of employees in accordance with what is desired by the institution concerned. Every training as an effort to achieve an increase in the work productivity of a company cannot be separated from influences, both from within and from outside the agency. This influence requires every organization to improve services so that it can meet the increasing needs of society. The purpose of this research is to find out and analyze the effect of training on employee performance at PT Tempo Tbk Palembang. The type of research used is quantitative descriptive research. Data collection method using a questionnaire. The sampling technique used saturated sampling with a total sample of 90 people. The analysis technique used is a simple linear regression analysis. The results of the study prove that training has a significant effect on employee performance at PT Tempo Tbk Palembang. This means that the employees at PT Tempo Tbk Palembang really need training so that they can be better in terms of performance at the company, the better the training provided the higher the employee performance. Keywords: Training; Performance; Employee